rs3764435 Associated With Parkinson's Disease in Mexican Mestizos: Case-Control Study Reveals Protective Effects Against Disease Development and Cognitive Impairment - Salas-Leal, Alma C.; Sandoval-Carrillo, Ada; Romero-Gutiérrez, Elizabeth; Castellanos-Juárez, Francisco X.; Méndez-Hernández, Edna M.; La Llave-León, Osmel; Quiñones-Canales, Gerardo; Arias-Carrión, Oscar; Salas-Pacheco, José M. (Frontiers in Neurology, 2019)
Parkinson’s disease (PD) is the second most common movement disorder. Genetic risk factors provide information about the pathophysiology of PD that could potentially be used as biomarkers. The ALDH1A1 gene encodes for the aldehyde dehydrogenase enzyme, which is involved in the disposal of toxic metabolites of dopamine. Due to the cytotoxic nature of aldehydes, their detoxification is essential for cellular homeostasis. It has been reported that ALDH1A1 expression levels and activity are decreased in PD patients. A deficit in ALDH1A1 activity in the substantia nigra, may lead to the accumulation of neurotoxic aldehydes and eventually the cell death seen in PD. One of the single nucleotide polymorphisms (SNP) that may modulate ALDH1A1 activity levels is rs3764435 (A/C). To investigate whether a statistical association exists between PD and the SNP rs3764435, we carried out a population-based Case-Control association study (120 PD patients and 178 non-PD subjects) in Mexican mestizos. DNA was extracted from blood samples and genotyped for rs3764435 using real-time PCR. A significant difference was found between PD cases and controls in both allelic and genotypic frequencies. The calculated OR showed that the C/C genotype is a protective factor under the codominant and recessive models of inheritance. However, after stratifying by sex, the protective role of this genotype is conserved only in men. Also, under the codominant and dominant models, rs3764435 appears to exert a protective effect against cognitive impairment in PD patients. Here for the first time, we show an association between PD and rs3764435 in a Mexican mestizo population, suggesting it confers neuroprotection for dementia in PD and is neuroprotective against developing PD in the males of this population. While analysis of the SNP looks favourable, replication of our study in cell lines or rs3764435 KO mice is required to validate these results.